(untitled) ("Conference on Universal Science Research 2023", 2026)
Inclusive education, which ensures equal access to quality education for all children regardless of their physical, intellectual, or social conditions, has become a global priority in modern educational systems. This study explores the educational, economic, and social impacts of inclusive education for children with disabilities. The research highlights how inclusive learning environments improve academic achievement, enhance social integration, and contribute to long-term economic benefits both for individuals and society.